1984
DOI: 10.1159/000225782
|View full text |Cite
|
Sign up to set email alerts
|

Cases of Carcinoma of Thyroid following Iodine-131 Therapy for Hyperthyroidism

Abstract: 2 cases of anaplastic thyroid cancer are described which developed after treatment of hyperthyroidism with iodine-131.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…From Doniach's work and the incidence of occult cancers it is not surprising that the patient developed a carcinoma for he had a persistent stimulus to the thyroid, albeit a thyroid stimulating immunoglobin rather than TSH, and he had been earlier treated with a small dose of 1311. Gossage et al 15 have reported a somewhat similar case who developed and died from an anaplastic carcinoma 23 years after 1311 therapy. Burke et al 16 also reported a 37 year old female who developed a follicular carcinoma 11 years after 1311 therapy, having been mildly hyperthyroid all the time.…”
Section: Discussionmentioning
confidence: 92%
“…From Doniach's work and the incidence of occult cancers it is not surprising that the patient developed a carcinoma for he had a persistent stimulus to the thyroid, albeit a thyroid stimulating immunoglobin rather than TSH, and he had been earlier treated with a small dose of 1311. Gossage et al 15 have reported a somewhat similar case who developed and died from an anaplastic carcinoma 23 years after 1311 therapy. Burke et al 16 also reported a 37 year old female who developed a follicular carcinoma 11 years after 1311 therapy, having been mildly hyperthyroid all the time.…”
Section: Discussionmentioning
confidence: 92%
“…38 In addition to these cellular effects, it also induces some histological changes. 47 Although, the causeeffect relationship between low-dose RAI treatment and development of anaplastic thyroid cancer cannot be proven, it is obvious that followup including US examinations should continue for life long in patients who received RAI for hyperthyroidism. Histological examination might reveal multiple adenomatous nodules, follicular atrophy and fibrosclerosis, prominent oncocytic changes with nuclear atypia, and interstitial lymphocytic infiltrates and macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…46 The interval between RAI and diagnosis of anaplastic thyroid cancer is more than 10 years in nearly all cases, reaching to 23 years in some. 47 Although, the causeeffect relationship between low-dose RAI treatment and development of anaplastic thyroid cancer cannot be proven, it is obvious that followup including US examinations should continue for life long in patients who received RAI for hyperthyroidism.…”
Section: Discussionmentioning
confidence: 99%
“…This cancer was elicited 12-20 years after RAI 131 [26][27][28]. The Cooperative Thyrotoxicosis Therapy Follow-up Study concluded that thyroid cancer after radioactive iodine ablation developed in those people receiving lower rather than higher doses of RAI 131 therapy [29].…”
Section: Discussionmentioning
confidence: 99%